2020
DOI: 10.3390/en13205419
|View full text |Cite
|
Sign up to set email alerts
|

Design of Kinetic-Energy Harvesting Floors

Abstract: Alternative energy generated from people’s footsteps in a crowded area is sufficient to power smart electronic devices with low consumption. This paper aims to present the development of an energy harvesting floor—called Genpath—using a rotational electromagnetic (EM) technique to generate electricity from human footsteps. The dynamic models of the electro-mechanical systems were developed using MATLAB®/Simulink to predict the energy performances of Genpath and help fine-tune the design parameters. The system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 12 publications
0
14
0
2
Order By: Relevance
“…Moreover, researchers recently addressed the design and feasibility of producing energy harvesting floors, highlighting their applicability to wireless sensors and IoT technologies. However, some problems, such as improving energy efficiency in both production and storage stages and adapting the floor displacement, were pointed to as research gaps [117,118]. For cycling, researchers also tested piezoelectric energy harvesting in a stationary exercise bicycle.…”
Section: Energy Harvestingmentioning
confidence: 99%
“…Moreover, researchers recently addressed the design and feasibility of producing energy harvesting floors, highlighting their applicability to wireless sensors and IoT technologies. However, some problems, such as improving energy efficiency in both production and storage stages and adapting the floor displacement, were pointed to as research gaps [117,118]. For cycling, researchers also tested piezoelectric energy harvesting in a stationary exercise bicycle.…”
Section: Energy Harvestingmentioning
confidence: 99%
“…Hence, a significant decline in yearly peak cooling and lighting energy consumption. Jintanawan et al [11] designed an energy harvesting floor that could convert mechanical energy from people's footsteps to electrical energy. Their outcome showed that the lead-screw model with 45 • lead angles coupled with a Genpath prototype-II with a 12-V-DC generator can generate up to 702 mJ which more average energy than others.…”
Section: Brief Overview Of the Contributions To This Special Issuementioning
confidence: 99%
“…This Special Issue of Energies on the subject of "Green Energy Technology" contains the successful invited submissions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. A total of 17 technical papers that cover diversified green energy technology-related research have shown critical results and contributed significant findings in biofuel production [1], energy-saving in buildings [2], wind energy [3], energy policy [4], electricity supply [5], a thermal-hydraulic system [6], fluidized bed reactor [7], green-supply chains [8], SI engine [9], renewable energy grid [10], kinetic energy harvest [11], green hydrogen utilization [12], water conservation [13], hydraulic power [14], Illumination Performance in buildings [15], community renewable energy [16], and heat transfer [17].…”
Section: Introductionmentioning
confidence: 99%
“…Purwarupa yang dibuat sangat bermanfaat karena dapat dipasang di setiap lantai rumah dan dengan sendirinya dapat digunakan sebagai sumber energi listrik untuk rumah tersebut. Purwarupa pemanen energi yang diambil dari gerakan kaki di lantai telah dikembangkan oleh Jintanawan et al (2020) dengan menggunakan teknik elektromagnetik rotasional dalam mengkonversi energi langkah kaki menjadi energi listrik. Sementara itu, penelitian yang diuraikan dalam makalah ini menggunakan deretan piezoelektrik di lantai kemudian dihubungkan dengan modul pemanen energi tipe tertentu sebelum disimpan dalam penyimpan energi.…”
Section: Rancang Bangun Purwarupa Energy Harvesting Menggunakan Piezo...unclassified